2022
DOI: 10.1002/slct.202202425
|View full text |Cite
|
Sign up to set email alerts
|

A Green and Easy Large Scale Method for Obtaining Graphene Nanoplatelets by Steam Explosion and Ultrasonic Exfoliation

Abstract: A novel physical process to obtain graphene nanoplatelets consisting of two principal steps, steam explosion and ultrasonic exfoliation, is proposed. This approach requires only water; nevertheless, the pressure and temperature conditions in the steam explosion equipment contribute to the delamination of the graphite complemented with an ultrasonic step. Moreover, two kinds of source material were tested: highly pyrolytic oriented graphite and a lower oriented graphite. Infrared and energy dispersive x‐ray spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Separation of supernatant from sediment ensures the collection of few layers graphene; however, the quantity of obtained materials is limited. Some applications require the notable properties of these materials, but it has been reported that graphene‐related materials of higher thickness also improve the performance of different systems, mainly polymer nanocomposites 30,31 . Therefore, if sediment of hybrids is partially exfoliated, it could be a good option to reinforce polymers, for example epoxy matrices which are widely used in industry.…”
Section: Introductionmentioning
confidence: 99%
“…Separation of supernatant from sediment ensures the collection of few layers graphene; however, the quantity of obtained materials is limited. Some applications require the notable properties of these materials, but it has been reported that graphene‐related materials of higher thickness also improve the performance of different systems, mainly polymer nanocomposites 30,31 . Therefore, if sediment of hybrids is partially exfoliated, it could be a good option to reinforce polymers, for example epoxy matrices which are widely used in industry.…”
Section: Introductionmentioning
confidence: 99%